IDENTIFIKASI FORMALIN PADA KUNYIT GILING DI PASAR PANAM KOTA PEKANBARU MENGGUNAKAN PEREAKSI SCHIFF - Denia Pratiwi; Wahyu Margi Sidoretno (LPPM Universitas Abdurrab, 2018)
Formalin or commonly referred to as formaldehyde is a clear liquid, colorless or almost colorless, piercing smell, steam stimulates the mucous membrane of the nose and throat. The use of formalin as a food preservative is prohibited in the Regulation of the Minister of Health of the Republic of Indonesia Number 033 of 2012, because formalin is toxic (poison). This study identified formalin content in ground turmeric using Schiff reagent. The sample used is ground turmeric which is produced in the market at Panam, Pekanbaru. The purpose of this study was to determine whether milled turmeric produced at the Panam Market in Pekanbaru city contained formaldehyde. This method research qualitative analysis and was conducted at the Anafarma Laboratory of Abdurrab University in January 2017. From the results of the research that has been done, it was obtained from 10 test samples, 3 of which were positive formalin.